Unextracted cottonseed in diets for monogastric animals. II. The effect of boiling and oven vs sun drying following pretreatment with a ferrous sulfate solution - Clawson, AJ; Maner, JH; Gómez G., Guillermo G.; Flores, Z; Buitrago, J.A. (1975)
Rats fed a corn base diet supplemented with dehulled cottonseed kernels which were boiled in a ferrous sulfate solution for 30 min gained as rapidly and required no more feed per unit of gain than those fed a corn-soybean meal diet. Boiling cottonseed kernels in the absence of ferrous sulfate greatly improved its nutritive value, however, boiling for 1 hr did not improve the cottonseed as much as mixing it with a cold (17 C) ferrous sulfate solution followed by oven drying at 70 C. Sun drying of either cottonseed meats or whole cottonseed (pretreated in a ferrous sulfate solution) was equal to oven drying in promoting rat growth. Similar results were obtained when these principles were applied to cottonseed meats used in pig diets; i.e., pigs fed diets containing cottonseed meats pretreated with ferrous sulfate solution followed by either sun or oven drying performed as well as those fed the corn-soybean meal control diet.